Microstructured optical fibres in chalcogenide glass - Li, Qingquan (2013)
Chalcogenide glasses offer transmission windows within the far-visible, near- and mid-infrared (IR) range. They exhibit potentially excellent linear and large nonlinear optical properties, photosensitivity and their low phonon energies are conducive to efficient dopant rare earth transitions. These properties enable many potential infrared applications: large-scale optics; fibreoptics; integrated optics; optical imaging; optical data storage and all-optical switching. Two lines of experimental work were followed in this project based on chalcogenide glasses, as below: (1) Antimony was used to replace arsenic, to form the ternary Ge-Sb-Se glass system. Nine compositions of Ge-Sb-Se glasses were synthesised and characterised to reveal their glass forming abilities, thermal properties and optical properties. Glass pairs, with close thermal properties and relatively high refractive index contrast, were developed for fabricating core-clad. structure step index fibre and microstructured optical fibres (MOFs). (2) Fabrication of an all-solid chalcogenide glass microstructured fibre (MOF), which was designed as a mimic of the holey suspended structure silica MOF, was carried out. A cane-drawing technique and a real-time contactless diameter monitor of the chalcogenide canes were developed to improve the precision of the fabrication. Stacking equipment was designed to improve the technique of the chalcogenide preform stacking.